Predominance of the use of Clonazepam in patients of a Basic Health Unit in the city of Mossoró – RN (Research, Society and Development, 2020)
Anxiety – related disorders are a disease commonly identified in the Brazilian population. It is estimated that about 18.6 million people are addicted to benzodiazepines. Among the complaints reported by patients, we can identify anxiety disorders, mental suffering and vulnerability factors that arise dynamically throughout the life of each person. Thus, the present study aimed to track the epidemiological profile and the type of psychotherapy used in the treatment of patients who are part of the mental health group of a Basic Health Unit (UBS) in the city of Mossoró – RN. For this, a cross-sectional, descriptive, retrospective study with a quantitative approach was carried out, with the target population being all patients who made and use psychotropic medication in the Unit in question. Thus, of a total of 573 medical records present at the UBS, 36 fit as users of psychotherapeutic drugs, reflecting 6.28% of users of the health system. It was observed that the most prevalente age group using psychotropic drugs are between 60 – 69 years of age, constituting 36.11% of users. There is a discrepancy in the use of Clonazepam (with 55.5%) in relation to other drugs. There was also a prevalence of the use of psychiatric drugs by women and patients aged over 40 years. Thus, the present work proposes intervention measures to rationalize the use of psychotropic drugs, aiming at the participatory inclusion of the patient in the health system.